Insectívoros (Erinaceomorpha, Soricomorpha, Mammalia) del Rambliense del área de Daroca-Calamocha - Van Den Hoek Ostende, Lars W. (Coloquios de Paleontología, 2003)
The insectivore assemblages from the Ramblian stratotype near Calamocha (Spain) are described, as well as those from San Roque 4A and 4B, two Ramblian localities near the Aragonian stratotype. Two new species are described, the erinaceid Galerix remmerti, and the shrew Clapasorex alvarezae. Both the percentages and the diversity of insectivores are higher in the Lower Ramblian, suggesting more humid conditions in zone Z than in zone A. This is in contradiction with the palaeoenvironmental reconstructions based on rodents.